The work of Ukrainian and Polish writers in the context of the literary process of the 19th century (using the example of the work of Olga Kobylianska and Eliza Ożeszko) - Demchenko, Natalia; Chala, Anna; Yaitska, Darya (V. N. Karazin Kharkiv National University Bulletin History of Ukraine. Ukrainian Studies: Historical and Philosophical Sciences, 2024)
Research aim. The article attempts to elucidate the peculiarities of artistic modeling of female characters in the works of Olha Kobylianska and Eliza Orzeszkowa in the context of the Ukrainian-Polish literary dialogue of the nineteenth century.Methodology of the research. The study is based on analytical review, aspectual analysis, elements of psychoanalysis, comparative analysis, mythological analysis, intertextual analysis, and the method of synthesis.The scientific novelty.  For the first time, the works of Ukrainian and Polish writers Olga Kobylianska and Eliza Orzeszkowa are comparatively studied; the peculiarities of linguistic modeling of women's images as a phenomenon of formation of gender-feminist, moral, ethical, socio-psychological, artistic, historical and national values in the context of the Ukrainian-Polish literary dialogue are revealed.Conclusions. The research is an attempt to characterize intercultural Ukrainian-Polish literary contacts of the nineteenth century not only in the historical and literary context, but also in the psycholinguistic context – through the artistic modeling of female characters in the works of Olga Kobylianska and Eliza Orzeszkowa, which makes it possible to trace the formation of gender-feminist, moral, ethical, socio-psychological, artistic, historical and national values of the two European countries. The article shows that the writers' works demonstrate a different vision of the topic of gender-feminist, moral, ethical, socio-psychological, artistic, historical and national orientation in texts of traditional and feminist nature. Each of the authors has her own style, views on life's problems and their solutions, and relies on her own life experience, using her own artistic means. We see the prospect of the study in the characterization of the onomastic element in the idiom of the writers.